DETERMINAN KEJADIAN ASFIKSIA NEONATORUM DI RUMAH SAKIT IBU DAN ANAK (RSIA) PEMERINTAH ACEH - Eristono; Erly Mauvizar; Amalia (Rena Cipta Mandiri, 2025)
Background: Asphyxia is one of the causes of neonatal death. The causes of neonatal asphyxia consist of: maternal factors, placental factors, fetal factors and delivery factors. Research Objectives: To determine the determinants of neonatal asphyxia at the Aceh government Mother and Child Hospital (RSIA). Research Methods: This research design uses a case control study with a retrospective approach. The population in this study were all newborns registered in the NICU room register at the Aceh Government Mother and Child Hospital (RSIA) for 2019-2022. The case sample in the case sampling technique was total sampling with a total of 186 newborns who experienced asphyxia. Results: The results of statistical tests showed that maternal age, amniotic fluid mixed with meconium, prolonged labour, and type of delivery with a p value <0.05, which means that there is a relationship with the incidence of asphyxia in newborns. The results of statistical tests on breech position and placenta previa showed a p value > 0.05, which means that there was no association with the incidence of asphyxia in newborns. The most influential factor with the incidence of asphyxia was amniotic fluid mixed with meconium with an OR value of 3.798. Conclusion: There is a need to increase the ability of midwives to provide delivery services and assistance, especially in cases of amniotic fluid mixed with meconium through education and training both internally and externally through seminars or special training.